Joshua A. Fogel (editor y traductor). Recent Japanese Studies of Modern Chinese History. Edición especial de Chinese Studies in History, Nueva York, otoño-invierno, 1984-1985, vol. xviii, num. 12 M.E. Sharpe, 1984. 235 pp. - Cornejo Bustamante, Romer (Estudios de Asia y África, 1985)
-